2020
DOI: 10.1371/journal.pone.0240452
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of respiratory virus in pulmonary exacerbations of children with Cystic Fibrosis

Abstract: Backgrounds Cystic Fibrosis (CF) is a genetic, multisystemic, progressive illness that causes chronic suppurative lung disease. A major cause of morbimortality in this condition are pulmonary exacerbations. Although classically attributed to bacterial infections, respiratory virus have been increasingly recognized in its ethiopathogeny. Methods Nasopharyngeal swab samples were collected from children < 18 years old with CF in Rio de Janeiro, Brazil, with pulmonary exace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…1 The impact of these measures on cystic fibrosis (CF) pulmonary exacerbations (PEx) has not been described. Respiratory viral infections are a common trigger for PEx, 2,3 and COVID-19 restrictions might lead to fewer PEx by reducing exposure to viruses in general, not just SARS-CoV2. To test the hypothesis that the COVID-19 lockdown would be associated with a lower PEx incidence we compared PEx data at our CF Center from the time with the most stringent restrictions in Indiana to the same time interval in 2019.…”
Section: Covid-19 Cystic Fibrosis Epidemiology Exacerbationmentioning
confidence: 99%
“…1 The impact of these measures on cystic fibrosis (CF) pulmonary exacerbations (PEx) has not been described. Respiratory viral infections are a common trigger for PEx, 2,3 and COVID-19 restrictions might lead to fewer PEx by reducing exposure to viruses in general, not just SARS-CoV2. To test the hypothesis that the COVID-19 lockdown would be associated with a lower PEx incidence we compared PEx data at our CF Center from the time with the most stringent restrictions in Indiana to the same time interval in 2019.…”
Section: Covid-19 Cystic Fibrosis Epidemiology Exacerbationmentioning
confidence: 99%
“…An investigation of 452 children with acute respiratory infection reported that acute respiratory infection in children was mainly infected by HRV (11.28%), and most of the HRV infection occurred was in winter 7 . Respiratory virus surveillance studies showed that the positive rate of HRV was 16.4%–35.1% 8–13 . During the COVID‐19 pandemic, the government had taken all possible means to stop the pandemic, and successfully stopped the COVID‐19 pandemic in Guangzhou, and the common respiratory infectious diseases, such as influenza and pneumonia as well 3 .…”
Section: Characteristics School a School B School C School D School Ementioning
confidence: 99%
“…During the same period, reduced respiratory morbidity was demonstrated in other pediatric chronic lung diseases, where respiratory viral infections are a common trigger of pulmonary exacerbations, suggesting that COVID‐19 restrictions might have led to reduced exposure to viruses in general, not just SARS‐CoV2 24,25 . Unfortunately, laboratory testing for respiratory viruses was not part of our study protocol and data on viral infections pre‐ and during the lockdown measures period were only available through questionnaire responses.…”
Section: Discussionmentioning
confidence: 99%